Sugar Taxes and Changes in Total Calorie Consumption: A Simple Framework - John Creedy (New Zealand Government, The Treasury, 2016)
This paper demonstrates the potential importance, when considering total calorie intake, of allowing for the substitution effects of imposing a selective tax on a commodity having a high sugar content, when non-taxed commodities exist and also have relatively high calorie content. A framework is presented which allows the elasticity of calorie consumption with respect to a price change to be derived. This brings out the role of relative budget shares, relative calorie content of goods and relative prices to be clearly seen, along with own- and cross-price elasticities. Their absolute values for each commodity group are not required. It is demonstrated that the focus of attention needs to be much wider than a simple concentration on the own-price elasticity of demand for the commodity group for which a sumptuary tax is envisaged.
Keywords: I10; H2; H31; 330; Sugar-sweetened beverage; calorie intake; demand elasticity; Zucker; Steuer; Konsumentenverhalten; Ernährungsverhalten; Steuerwirkung; Preiselastizität; Neuseeland